KINERJA DAUR ULANG CAMPURAN DINGIN DENGAN ASPAL BUSA PADA LALU LINTAS BERAT - Djoko Widajat; M. Sjahdanulirwan (Direktorat Bina Teknik Jalan dan Jembatan, 2009)
Cold recycling is one of technology alternative which can be prefend in selecting the strategy alternative for road rehabilitation project. Learning about the development technology. we also learn about the weaknesses of it. The pavement assessment condition, which sustain heavy traffic laod in the road trial, has been identified. In order to evaluate the performance of recycling technology, laboratory testing for material properties, mixture as well as field observation have been conducted. The evaluatiins consist of material properties, mixture, construction and pavement performance since the opening traffic until the age of construction in approximately 2 years. The result of laboratory test shows that the mixture strength criteria meet the specification, whereas the field assessment based on functional condition and from structural pavement indicates that pavement performance decreases, this shown by occuring rutting in the some parts of the wheel track. Based from this result, it is predicted that there is a correlation between material, mixture and construction method and pavement service life. The construction method should be developed in the future to minimize early deterioration. This paper describes about the evaluation result for recycling technology with binder material of foam bitumen which have been used in road link with heavy traffic load Jatibarang - Palimanan, Panturan, West Java. Key word : cold mix, recycling, foam bitumen, RFB (Recycling by Foam Bitumen) , pavement performance.